A proposed metadiscourse framework for lay ESL writers - Tan, Helen; Chan, Swee Heng; Abdullah, Ain Nadzimah (IDOSI Publications, 2012)
In the past two decades, writing scholars [1-3] have tried to make sense of the functions and forms of metadiscourse in writing. In doing so, each of these scholars have designed varied metadiscourse frameworks that illustrate the different categories, functions and linguistic realizations so as to capture the use of metadiscourse more succinctly. The intention of this study is to review existing metadiscourse frameworks and to plug the gap that could exist for a more comprehensive framework for effective use by lay ESL writers. The underlying postulation is that various frameworks may have different assumptions, and thus to meet the needs of lay ESL writers, a different approach is likely needed.